Chemical Constituents of Snake Fruit (Salacca zalacca (Gaert.) Voss) Peel and in silico Anti-aging Analysis - Ermi Girsang; I Nyoman Ehrich Lister; Chrismis Novalinda Ginting; Adrian Khu; Butter Samin; Wahyu Widowati; Satrio Wibowo; Rizal Rizal (Cell and BioPharmaceutical Institute, 2019)
Background: Skin aging is a condition where skin is unable to retain both its physiological and structural integrity. Plants is the main source of phtytochemicals compound with wide range of biological activities. Through the efforts of ongoing scientific researches, an increasing number of plant extracts and phytochemicals have been showed promising result as anti-aging agent. Snake fruit (Salacca zalacca (Gaert.) Voss) is tropical plant belongs to the palm tree family (Arecaceae) that served as important crop in Indonesia. Despite its utilization, the phytochemical compound available in snake fruit, especially its peel have not been well documented. Present study aimed to elucidate the phytochemical constituent of snake fruit peel and its anti-aging potency.Materials and Methods: Snake fruit peel extract (SPE) was subjected to qualitative phytochemical assay, high performance liquid chromatography, and molecular docking towards protein related in skin aging.Results: The screening showed SPE contained phytochemical compound belong to flavonoid, tannin, phenol, triterpenoid, saponin and alkaloid. Thus, based on the analysis only chlorogenic acid was present in SPE whilst rutin and caffeic acid were not detected. The SPE was contained chlorogenic acid around 1.074 mg/g dry weight. Chlorogenic acid had the high binding affinity towards matrix metalloproteinase (MMP)-1 (-9.4 kcal/mol).Conclusion: Current findings may provide scientific evidence for possible usage of SPE and its compounds as antioxidant and anti-aging agent.Keywords: Salacca zalacca, phytochemical compound, high performance liquid chromatography, anti-aging